2017
DOI: 10.1097/txd.0000000000000743
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of the Shift Toward Donation After Circulatory Death in Australia

Abstract: BackgroundIn recent years, an increasing number of donor livers are being declined for transplantation in Australia. The aim of this study was to evaluate the impact of donation after cardiac death and other factors associated with organ quality on liver utilization rates in Australia.MethodsData on organ donors who donated at least 1 organ between 2005 and 2014 were obtained from the Australia and New Zealand organ donation registry. Temporal changes in donor characteristics were assessed and a logistical reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Organ donation has steadily increased over the past few years and this is in part attributable to a rise in DCD donor numbers 1,17,18 . Many potential DCD donors are not recognised in Australia 19 and healthcare practitioners' understanding and attitudes towards this practice may play a role [11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…Organ donation has steadily increased over the past few years and this is in part attributable to a rise in DCD donor numbers 1,17,18 . Many potential DCD donors are not recognised in Australia 19 and healthcare practitioners' understanding and attitudes towards this practice may play a role [11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…(17) Our early results show that NMP can safely increase the utilization rate. (18) In the preclinical study, 7 (70%) discarded livers showed favorable metabolic and perfusion characteristics. Subsequently, post-SCS NMP was applied to preserve and assess 10 orphan livers, all of which were successfully transplanted with 100% 6-month graft and patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, most programs offer ECD organs to potential recipients disadvantaged by current allocation policy. (1,2) SCS reduces an organ's metabolic activity. The resulting oxygen level compromises mitochondrial metabolism with an accumulation of toxic metabolites.…”
Section: See Article On Page 1618mentioning
confidence: 99%